The impact of different natural environments on the regeneration dynamics of two Nothofagus species across elevation in the southern Andes - Cagnacci, Julieta María; Estravis Barcala, Maximiliano; Lia, Veronica Viviana; Martinez Meier, Alejandro; Gonzalez Polo, Marina; Arana, María Veronica (Forest Ecology and Management, 2020)
A widely accepted paradigm in forest ecology proposes that patterns of relative abundance among mature forest trees are largely influenced by biotic and abiotic processes that operate most intensely during the earliest lifecycle stages. Therefore, traits expressed early in development such as germination and seedling establishment may be under strong selective pressure from the environment, and their adjustment to changing climates may ultimately influence species’ responses to global climate change. Here we used different environments established across altitude in an old-growth temperate Patagonian forest as a natural laboratory, and studied the Nothofagus obliqua and N. pumilio regeneration response – seedling emergence and survival –to different climatic scenarios, inside and outside their natural distribution range. These are two iconic species of sub-Antarctic forests, which co-exist in contrasting and non-overlapping thermal niches. Whereas N. obliqua is predominant in the warmer and lower environments at 650–850 m above sea level (a.s.l.), N. pumilio inhabits the colder and higher montane environments, above 1000 m a.s.l. By sowing germinated seeds of both species at different altitudes in the forest – 680, 930 and 1340 m a.s.l. – we were able to distinguish the environmental influence on seedling emergence from its influence on germination. Our results show that the local environment had a major effect on seedling survival, and a minor influence on emergence. Overall, regeneration of both species showed a temporal window of stronger environmental susceptibility, which comprised the process of emergence, and in the particular case of N. obliqua, the first month of post-emergence growth. Survival ability was influenced by the ontogenetic stage of the seedling, evidencing stronger environmental resistance and higher probability of survival after the first year of growth. Interestingly, we found inter-specific differences in survival dynamics and the final number of surviving seedlings, which may reflect species-specific physiological adaptations and tolerance to abiotic stress. However, the performance of both species was favored in relatively colder environments inside their natural ranges. This indicates that present climatic conditions in the lower zones of the gradient exert physiological constraints at seedling stage, even in N. obliqua, which shows high abundance of adult trees at these altitudes. Results reported here were consistent across two independent experiments and will be discussed in the context of forest regeneration in present and future climatic scenarios. Estación Experimental Agropecuaria Bariloche Fil: Cagnacci, Julieta María. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Bariloche. Instituto de Investigaciones Forestales y Agropecuarias Bariloche. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Instituto de Investigaciones Forestales y Agropecuarias Bariloche; Argentina Fil: Estravis Barcala, Maximiliano. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales. Universidad Nacional del Comahue. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales; Argentina Fil: Lia, Veronica Viviana. Instituto Nacional de Tecnología Agropecuaria (INTA). Instituto de Agrobiotecnología y Biología Molecular. Consejo Nacional de Investigaciones Cientificas y Tecnicas; Argentina Fil: Martinez Meier, Alejandro. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Bariloche. Instituto de Investigaciones Forestales y Agropecuarias Bariloche. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Instituto de Investigaciones Forestales y Agropecuarias Bariloche; Argentina Fil: Gonzalez Polo, Marina. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Universidad Nacional del Comahue. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina Fil: Arana, María Verónica. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Bariloche. Instituto de Investigaciones Forestales y Agropecuarias Bariloche. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Instituto de Investigaciones Forestales y Agropecuarias Bariloche; Argentina